Religion and family planning. (1st November 2016) - Pinter, Bojana; Hakim, Marwan; Seidman, Daniel S.; Kubba, Ali; Kishen, Meera; Di Carlo, Costantino
Abstract: Religion is embedded in the culture of all societies. It influences matters of morality, ideology and decision making, which concern every human being at some point in their life. Although the different religions often lack a united view on matters such contraception and abortion, there is sometimes some dogmatic overlap when general religious principles are subject to the influence of local customs. Immigration and population flow add further complexities to societal views on reproductive issues. For example, present day Europe has recently faced a dramatic increase in refugee influx, which raises questions about the health care of immigrants and the effects of cultural and religious differences on reproductive health. Religious beliefs on family planning in, for example, Christianity, Judaism, Islam and Hinduism have grown from different backgrounds and perspectives. Understanding these differences may result in more culturally competent delivery of care by health care providers. This paper presents the teachings of the most widespread religions in Europe with regard to contraception and reproduction.